Pushed : miners, a merchant, and (maybe) a massacre - Spagna, Ana Maria (Torrey House Press, 2023)
"Amid an alarming rise in xenophobia, Ana Maria Spagna stumbled upon a story: one day in 1875, on a high bluff over the Columbia River, a group of local Indigenous people murdered a large number of Chinese Miners and pushed their bodies off a cliff into the river. The incident was dubbed the Chelan Falls Massacre. Despite having lived in the area for decades, Spagna had never before heard of this event. In Pushed, she sets out to discover what really happened and why. Her eye-opening investigative journey replaces convenient narratives of the American West with nuance and complexity, revealing the danger in forgetting or remembering atrocities when history is murky and asking what allegiance to a place requires"--Back cover.